High-performance hydrogenated butadiene-isoprene elastomer as well as preparation method and application thereof
By using Wilkinson catalyst RhCl(PPh3)3 complex for hydrogenation catalysis, high-performance hydrogenated butadiene-isoprene elastomer was prepared, which solved the production barriers in the high-temperature solution polymerization process and achieved the preparation of materials with high hydrogenation degree and excellent mechanical properties.
Patent Information
- Application Number
- CN202410454785.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-04-16
- Publication Date
- 2025-10-24
AI Technical Summary
The existing high-temperature solution polymerization process has production barriers in the preparation of high-performance polyolefin elastomers, especially the immature catalytic system, which leads to poor material performance.
Wilkinson catalyst RhCl(PPh3)3 complex is used for hydrogenation catalysis, butadiene-isoprene copolymer is prepared through coordination polymerization system, and hydrogenation reaction is carried out under specific conditions to obtain high-performance hydrogenated butadiene-isoprene elastomer.
A hydrogenated butadiene-isoprene elastomer with a hydrogenation degree greater than 90% was obtained, which has excellent mechanical properties and chemical stability, can replace EPDM rubber, and has broad application prospects.
Smart Images

Figure CN120829549A_ABST
Abstract
Description
TECHNICAL FIELD
[0001] The present application belongs to the field of polyolefin elastomer preparation, and particularly relates to a high-performance hydrogenated butadiene-isoprene elastomer and a preparation method and application thereof. BACKGROUND
[0002] Polyolefin elastomer generally refers to a copolymer of ethylene and propylene or other alpha olefins (such as 1-butene, etc.), which is prepared by solution polymerization at a temperature above the melting point of the polymer using a metallocene catalyst system.
[0003] The high-temperature solution polymerization process is not mature, and therefore, it is necessary to develop a catalyst system and subsequent treatment process to effectively solve the production barriers of high-performance polyolefin elastomer. SUMMARY
[0004] To overcome the above technical problems, the present application provides a high-performance hydrogenated butadiene-isoprene elastomer and a preparation method and application thereof.
[0005] The technical solution of the present application is as follows:
[0006] One of the purposes of the present application is to provide a high-performance hydrogenated butadiene-isoprene elastomer, which has a number average molecular weight of 10,000-700,000 g / mol, a molecular weight distribution of 1.0-5.0, a hydrogenation degree of > 90%, and a glass transition temperature range of -80 to -20℃.
[0007] Further limitation, the elastomer has a number average molecular weight of 10,000-500,000 g / mol, a molecular weight distribution of 2.1-2.8, a hydrogenation degree of > 92%, and a glass transition temperature range of -70 to -25℃.
[0008] Further limitation, the elastomer has a mechanical property of Shore A hardness > 40, a tensile strength > 10 MPa, an elongation at break > 270%, a 300% modulus > 10 MPa, and a tear strength > 20 N / mm.
[0009] Further limitation, the elastomer has a mechanical property of Shore A hardness > 46, a tensile strength > 13 MPa, an elongation at break > 280%, a 300% modulus > 12 MPa, and a tear strength > 23 N / mm.
[0010] The second purpose of the present application is to provide a preparation method of a high-performance hydrogenated butadiene-isoprene elastomer, which comprises the following steps:
[0011] The butadiene-isoprene copolymer is dissolved in a solvent to form a mother liquor, which is added into a high-temperature reaction kettle under an argon atmosphere, followed by adding a Wilkinson catalyst and triphenylphosphine in sequence, and then hydrogen is used to replace the gas in the kettle, and the hydrogenation reaction is carried out at a rotation speed of 100-1000 rpm, a pressure of 10-90 mbar, and a temperature of 60-150℃ for 1-24 h. After the reaction is completed, the precipitate is cooled, precipitated, and vacuum-dried at room temperature to obtain a high-performance hydrogenated butadiene-isoprene elastomer.
[0012] Further limited, the block ratio of isoprene to butadiene in the butadiene-isoprene copolymer is (1-9):1.
[0013] Further limited, the concentration of the butadiene-isoprene copolymer in the mother liquor is 1-3 wt%.
[0014] Further limited, the concentration of the butadiene-isoprene copolymer in the mother liquor is 2 wt%.
[0015] Further limited, the preparation method of the butadiene-isoprene copolymer:
[0016] Under anhydrous and anaerobic conditions, an iron catalyst, a cocatalyst, an olefin monomer, and an anhydrous solvent are added into a reactor, and the polymerization reaction is stirred at 0-100℃ for 10-120 min. After the reaction is completed, a quenching agent and an anti-aging agent are added, and then washed and vacuum-dried to constant weight to obtain the butadiene-isoprene copolymer.
[0017] Further limited, the iron catalyst is any one of the following structural formulas:
[0018]
[0019] Further limited, the molar ratio of the olefin monomer to the iron element in the iron catalyst is (10-20000):1.
[0020] Further limited, the molar ratio of the olefin monomer to the iron element in the iron catalyst is (260-6600):1, the temperature of the polymerization reaction is 30℃, and the time is 30 min.
[0021] Further limited, the Wilkinson catalyst is chloro(triphenylphosphine)rhodium, the molar ratio of chloro(triphenylphosphine)rhodium to triphenylphosphine is 1:(1-20), and the solvent is one or more of toluene, xylene, n-hexane, and cyclohexane.
[0022] Further limited, the molar ratio of chloro(triphenylphosphine)rhodium to triphenylphosphine is 1:9, the temperature of the hydrogenation reaction is 100-120℃, the pressure is 60-80 mbar, the rotation speed is 660 rpm, and the time is 16 h.
[0023] The third object of the present application is to provide an application of the high-performance hydrogenated butadiene-isoprene elastomer in the viscosity index improver, automobile parts and insulating material field.
[0024] Compared with the prior art, the present application has the following advantages:
[0025] (1) The present application uses Wilkinson catalyst as the hydrogenation catalyst to hydrogenate the double bond of the butadiene-isoprene copolymer obtained by the coordination polymerization system, and finally obtains a hydrogenated butadiene-isoprene elastomer material, thereby providing a new way to obtain a hydrogenated material and effectively solving the problems that have plagued the production of polyolefin elastomers.
[0026] (2) The present application provides a new type of hydrogenated butadiene-isoprene elastomer material, which has a number average molecular weight of 1.0-700,000 g / mol, a molecular weight distribution of 1.0-5.0, a hydrogenation degree of more than 90%, a glass transition temperature range of the elastomer of -80℃ to -20℃, a Shore hardness A of more than 40, a tensile strength of more than 10 MPa, an elongation at break of more than 270%, a 300% modulus of more than 10 MPa, and a tear strength of more than 20 N / mm.
[0027] (3) The present application optimizes the hydrogenation reaction conditions, reduces the hydrogenation pressure and temperature, and increases the amount of the cocatalyst, thereby effectively ensuring the hydrogenation activity of the catalyst, greatly improving the hydrogenation degree of the butadiene-isoprene copolymer, stably maintaining the hydrogenation yield at more than 83%, and avoiding the breakage of the polymer chain during the hydrogenation process. The molecular chain of the hydrogenated elastomer is composed of C-H single bonds, and the structure is similar to that of the ethylene-propylene rubber. The hydrogenated elastomer has good chemical stability and mechanical properties, and has a wide application prospect and certain substitutability for the ethylene-propylene rubber. Meanwhile, the ethylene-propylene rubber has a low strength and must be reinforced to have a use value, while the hydrogenated elastomer obtained by the present application has a relatively high strength and can be used without reinforcement.
[0028] (4) The present application is based on the coordination iron catalytic system, and has the characteristics of low cost, simple operation and environmentally friendly components in the butadiene-isoprene copolymerization part. The system has high catalytic activity, and the monomer conversion rate can reach more than 99%. The coordination iron catalytic system has high solubility and can form a uniform solution reaction system. BRIEF DESCRIPTION OF DRAWINGS
[0029] Figure 1 The 1HNMR spectrum of the butadiene-isoprene copolymer obtained in step (1) of Example 1;
[0030] Figure 2GPC spectrum of the hydrogenated butadiene-isoprene elastomer obtained in Example 1.
[0031] Figure 3 GPC spectrum of the hydrogenated butadiene-isoprene elastomer obtained in Example 1.
[0032] Figure 4 DSC spectrum of the hydrogenated butadiene-isoprene elastomer obtained in Example 1.
[0033] Figure 5 Mechanical property test result spectrum of the hydrogenated butadiene-isoprene elastomer obtained in Example 1.
[0034] Figure 6 GPC spectrum of the hydrogenated butadiene-isoprene elastomer obtained in Comparative Example 1. DETAILED DESCRIPTION
[0035] The high mechanical property hydrogenated butadiene-isoprene elastomer of the present application has a number average molecular weight of 10,000-700,000 g / mol and a molecular weight distribution of 1.0-5.0, wherein the hydrogenation degree is > 90%, the glass transition temperature range is -80 to -20°C, the Shore hardness A is > 40, the tensile strength is > 10 MPa, the elongation at break is > 270%, the 300% modulus is > 10 MPa, and the tear strength is > 20 N / mm.
[0036] In a preferred embodiment, the elastomer has a number average molecular weight of 10,000-500,000 g / mol and a molecular weight distribution of 2.1-2.8, the hydrogenation degree is > 92%, the glass transition temperature range is -70 to -25°C, the Shore hardness A is > 46, the tensile strength is > 13 MPa, the elongation at break is > 280%, the 300% modulus is > 12 MPa, and the tear strength is > 23 N / mm.
[0037] The method for preparing the high mechanical property hydrogenated butadiene-isoprene elastomer of the present application is carried out in the following steps:
[0038] (1) Under anhydrous and anaerobic conditions, iron catalyst, cocatalyst, olefin monomer and anhydrous solvent are added to a reactor, and the polymerization reaction is stirred at 0-100°C for 10-120 min. After the reaction is completed, a quenching agent and an anti-aging agent are added, and after washing, vacuum drying is carried out to constant weight to obtain a butadiene-isoprene copolymer.
[0039] (2) dissolving the butadiene-isoprene copolymer obtained in step (1) in a solvent, and adding it into a high-temperature reaction kettle under an argon atmosphere, then adding a Wilkinson catalyst and triphenylphosphine in sequence, replacing the gas in the kettle with hydrogen, and then hydrogenating under the conditions of a rotation speed of 100-1000 rpm, a pressure of 10-90 mbar, and a temperature of 60-150 °C for 1-24 h, after which the reaction is cooled, the precipitate is separated, and vacuum drying is performed at room temperature to obtain a high-mechanical-property hydrogenated butadiene-isoprene elastomer.
[0040] In a preferred specific embodiment, in step (1): the block ratio of isoprene to butadiene in the butadiene-isoprene copolymer is (1-9): 1.
[0041] In a preferred specific embodiment, in step (1): the butadiene-isoprene copolymer is prepared by a method comprising:
[0042] Under anhydrous and anaerobic conditions, an iron catalyst, a cocatalyst, an olefin monomer, and an anhydrous solvent are added to a reactor, and the polymerization reaction is stirred at 0-100 °C for 10-120 min, after which a quenching agent and an anti-aging agent are added, washed, and vacuum dried to constant weight to obtain a butadiene-isoprene copolymer;
[0043] The iron catalyst is any one of the following structural formulas:
[0044]
[0045] The anhydrous solvent is one or more of toluene, xylene, chlorobenzene, petroleum ether, n-hexane, and cyclohexane;
[0046] The volume ratio of the olefin monomer to the anhydrous solvent is 1: (1-30), and is preferably 1:16;
[0047] The molar ratio of the olefin monomer to the iron element in the iron catalyst is (10-20000): 1, and is preferably (260-6600): 1;
[0048] The co-catalyst is single component or double component, when the co-catalyst is single component, the co-catalyst is one or several of MAO, DMAO and MMAO, the molar ratio of aluminum element in the co-catalyst to iron element in the iron catalyst is (100-1000):1, preferably 500:1, when the co-catalyst is double component, component A is selected from one or several of alkyl aluminum, component B is selected from one or several of MAO, DMAO, MMAO, 4-isopropyl-4'-methyl diphenyl iodonium tetra(pentafluorophenyl)borate, tris(pentafluorophenyl)phosphine, N,N-dimethyl anilinium tetra(pentafluorophenyl)borate, N,N-dihexadecyl anilinium tetra(pentafluorophenyl)borate, triphenylmethyl tetrafluoroborate, triphenyl phosphine oxide, triphenyl phosphine, tris(3-fluorophenyl)phosphine, tris(4-fluorophenyl)phosphine, wherein the alkyl aluminum is one or several of trimethyl aluminum, triethyl aluminum, triisobutyl aluminum, monochlorodiethyl aluminum, dichloroethyl aluminum, hemiethyl aluminum chloride, the molar ratio of aluminum element in component A to iron element in the iron catalyst is (1-100):1, preferably 40:1, the molar ratio of aluminum, boron or phosphorus element in component B to iron element in the iron catalyst is (1-20):1, preferably 1:1;
[0049] The temperature of the polymerization reaction is 30℃, and the time is 30 min.
[0050] The quenching agent is a mixed solution of concentrated hydrochloric acid and methanol, wherein the volume ratio of methanol to concentrated hydrochloric acid is (10-100):1, preferably 50:1, the anti-aging agent is an ethanol solution of 2,6-di-tert-butyl-4-methyl phenol with a mass concentration of 1%, and the volume ratio of the anti-aging agent to the solvent is 1:(1-50), preferably 1:25.
[0051] In the preferred specific embodiment, in step (2), the Wilkinson catalyst is chloro(triphenylphosphine)rhodium, and the molar ratio of chloro(triphenylphosphine)rhodium to triphenylphosphine is 1:(1-20), preferably 1:9.
[0052] In the preferred specific embodiment, in step (2), the solvent is one or several of toluene, xylene, n-hexane, and cyclohexane.
[0053] In the preferred specific embodiment, in step (2), the temperature of the hydrogenation reaction is 100-120℃, the pressure is 60-80 mbar, the rotation speed is 660 rpm, and the time is 16 h.
[0054] In order to make the purpose, technical scheme and advantages of the present application more clear, the present application is further described in detail below in combination with examples. It should be understood that the specific examples described herein are only used to explain the present application, and are not used to limit the present application.
[0055] The experimental methods used in the following examples are conventional methods unless otherwise specified. The materials, reagents, methods and instruments used, unless specifically stated, are conventional materials, reagents, methods and instruments in the art, which are available to those skilled in the art through commercial channels.
[0056] The mechanical property test standard in the following examples is GB / T 589-2009.
[0057] Example 1: The preparation method of a high-performance hydrogenated butadiene-isoprene elastomer in this example is as follows:
[0058] (1) Copolymerization part: Under argon atmosphere, 250 mL of Schlenk tube was sequentially added with anhydrous cyclohexane (67 mL), butadiene (1.07 g, 19.8 mmol, 1980 equiv.), isoprene (3.14 g, 46.2 mmol, 4620 equiv.), triethylaluminum (79.3 mg, 0.4 mmol, 40 equiv.), iron catalyst a (6.7 mg, 10 μmol, 1 equiv.), methylaluminoxane MAO (1.7 mg, 10 μmol, 1 equiv.), and polymerized at 30°C for 120 min, and then terminated with 25 mL of a mixed solution of methanol and hydrochloric acid (MeOH / HCl volume ratio = 50 / 1) and 1 mL of anti-aging agent. After the supernatant was poured out, the polymer was washed with ethanol three times, and the obtained polymer was placed in a vacuum oven at 40°C to dry to constant weight, to obtain a copolymer with a yield of >99%, and the 1H NMR spectrum is shown in Figure 1 , and the molecular weight information is shown in Table 1.
[0059] (2) Hydrogenation part: A 25 mL Schlenk tube was prepared with a xylene mother liquor of the copolymer (2 wt%). The reaction kettle was dried, and 15.0 mL of the xylene mother liquor of the copolymer (2 wt%), 20.4 mg g of triphenylphosphine (80 μmol, 9 equiv.), and 8.0 mg g of triphenylphosphine rhodium chloride (9 μmol, 1 equiv.) were added. H2 was replaced three times, and after the pressure was pumped to 60.0 mbar, stirring was started, the hydrogenation temperature was 100°C, the hydrogenation time was 16 h, and the rotation speed was 660 rpm. After the reaction was completed, the hydrogenation kettle was cooled to room temperature, and after the pressure was released, it was left to stand for 30.0 min, and then opened, poured into anhydrous ethanol and stirred, and the hydrogenated elastomer was separated in the form of a precipitate. Then the precipitate was placed in a vacuum oven at room temperature to dry to constant weight, and finally a white hydrogenated butadiene-isoprene elastomer was obtained, 1 , the 1H NMR spectrum is shown in Figure 2 , the GPC spectrum is shown in Figure 3 , and the mechanical property information is shown in Table 2.
[0060] Results: Hydrogenation yield: 87%, hydrogenation degree: >99%, hydride number average molecular weight (M n ):5.3×10 5 g / mol, molecular weight distribution (PDI): 2.4, and glass transition temperature is -49.3°C.
[0061] Figure 3 The glass transition temperature of the polymer in Example 1 is: starting point: -54.7°C, midpoint: -49.4°C, inflection point: -49.3°C, end point: -34.5°C, and specific heat change * :0.225 / (g*K).
[0062] Table 1 Molecular weight information
[0063] Peak M p (g / mol)]]> M n (g / mol)]]> M w (g / mol)]]> M z (g / mol)]]> M z+1 (g / mol)]]> M v (g / mol)]]> PD Peak1 1110733 531906 1297603 2163522 3330643 2013988 2.44
[0064] Table 2 Mechanical properties of hydrogenated products
[0065] Hardness / Shore A Tensile strength / MPa Elongation at break / % 300% modulus / MPa Tear strength N / mm 64 15.02 294.91 13.80 36.38
[0066] Example 2: This example differs from Example 1 in that the hydrogenation temperature in step (2) is 120°C, and the other steps and parameters are the same as those in Example 1.
[0067] Results: Copolymer yield: >99%, hydrogenation yield: 85%, hydrogenation degree: 99%, hydride number average molecular weight (M n ):4.66×10 5 g / mol, molecular weight distribution (PDI): 2.1, and glass transition temperature is -49.9° C. The mechanical properties of the hydrogenated product are shown in Table 3.
[0068] Table 3 Mechanical properties of hydrogenated products
[0069] Hardness / Shore A Tensile strength / MPa Elongation at break / % 300% modulus / MPa Tear strength N / mm 62 14.89 309.54 13.42 34.82
[0070] Example 3: This example differs from Example 1 in that the pressure in the reactor is increased to 80.0 mbar in step (2), and the other steps and parameters are the same as those in Example 1.
[0071] Results: Copolymer yield: >99%, hydrogenation yield: 83%, hydrogenation degree: 92%, hydride number average molecular weight (M n ):5.20×10 5 g / mol, molecular weight distribution (PDI): 2.7, and glass transition temperature is -48.6° C. The mechanical properties of the hydrogenated product are shown in Table 4.
[0072] Table 4 Mechanical properties of hydrogenated products
[0073] Hardness / Shore A Tensile strength / MPa Elongation at break / % 300% modulus / MPa Tear strength N / mm 63 14.02 297.38 14.32 35.48
[0074] Example 4: This example differs from Example 1 in that the amounts of each substance added in step (1) are changed to triethylaluminum (1.98 g, 10 mmol, 40 equiv.), iron catalyst a (167.5 mg, 0.25 mmol, 1 equiv.), methylaluminoxane MAO (42.5 mg, 0.25 mol, 1 equiv.), and the molecular weight of the resulting copolymer (M n ):0.2×10 5 g / mol, and other steps and parameters are the same as in Example 1.
[0075] Results: Copolymer yield: >99%, hydrogenation yield: 85%, hydrogenation degree: >99%, hydride number average molecular weight (M n ):0.16×10 5 g / mol, molecular weight distribution (PDI): 2.6, and glass transition temperature is -46.4° C. The mechanical properties of the hydrogenated product are shown in Table 5.
[0076] Table 5 Mechanical properties of hydrogenated products
[0077] Hardness / Shore A Tensile strength / MPa Elongation at break / % 300% modulus / MPa Tear strength N / mm 58 13.51 350.4 12.57 28.64
[0078] Example 5: This example differs from Example 1 in that the amounts of each substance added in step (1) are changed to triethylaluminum (172.4 mg, 0.87 mmol, 40 equiv.), iron catalyst a (14.57 mg, 21.73 μmol, 1 equiv.), methylaluminoxane MAO (3.7 mg, 21.73 μmol, 1 equiv.), and the molecular weight of the resulting copolymer (M n ):2.70×10 5 g / mol, and other steps and parameters are the same as in Example 1.
[0079] Results: Copolymer yield: >99%, hydrogenation yield: 86%, hydrogenation degree: >99%, hydride number average molecular weight (M n ):2.50×10 5 g / mol, molecular weight distribution (PDI): 2.7, and glass transition temperature is -48.6° C. The mechanical properties of the hydrogenated product are shown in Table 6.
[0080] Table 6 Mechanical properties of hydrogenated products
[0081] Hardness / Shore A Tensile strength / MPa Elongation at break / % 300% modulus / MPa Tear strength N / mm 60 13.69 310.3 13.76 29.34
[0082] Example 6: This example differs from Example 1 in that the co-catalyst system is a single component, the molar ratio of the aluminum element contained in the co-catalyst MAO to the iron element in the catalyst iron complex is 500:1, and the other steps and parameters are the same as in Example 1.
[0083] Results: Copolymer yield: >99%, hydrogenation yield: 87%, hydrogenation degree: >99%, hydride number average molecular weight (M n ):4.8×10 5 g / mol, molecular weight distribution (PDI): 2.6, and glass transition temperature is -47.9° C. The mechanical properties of the hydrogenated product are shown in Table 7.
[0084] Table 7 Mechanical properties of hydrogenated products
[0085] Hardness / Shore A Tensile strength / MPa Elongation at break / % 300% modulus / MPa Tear strength N / mm 63 15.26 297.48 14.16 35.97
[0086] Example 7: This example differs from Example 1 in that the block ratio of butadiene to isoprene in the copolymer obtained in step (1) is 1:9, and the other steps and parameters are the same as those in Example 1.
[0087] Results: Copolymer yield: >99%, hydrogenation yield: 85%, hydrogenation degree: >99%, hydride number average molecular weight (M n ):4.70×10 5 g / mol, molecular weight distribution (PDI): 2.8, and glass transition temperature is -26.8° C. The mechanical properties of the hydrogenated product are shown in Table 8.
[0088] Table 8 Mechanical properties of hydrogenated products
[0089] Hardness / Shore A Tensile strength / MPa Elongation at break / % 300% modulus / MPa Tear strength N / mm 46 13.48 364.28 12.35 23.26
[0090] Example 8: This example differs from Example 1 in that the block ratio of butadiene to isoprene in the copolymer obtained in step (1) is 9:1, and the other steps and parameters are the same as those in Example 1.
[0091] Results: Copolymer yield: >99%, hydrogenation yield: 85%, hydrogenation degree: >99%, hydride number average molecular weight (M n ):4.30×10 5 g / mol, molecular weight distribution (PDI): 2.6, and glass transition temperature is -67.5° C. The mechanical properties of the hydrogenated product are shown in Table 9.
[0092] Table 9 Mechanical properties of hydrogenated products
[0093] Hardness / Shore A Tensile strength / MPa Elongation at break / % 300% modulus / MPa Tear strength N / mm 69 19.48 285.28 16.35 37.26
[0094] Example 9: This example differs from Example 1 in that the block ratio of butadiene to isoprene in the copolymer obtained in step (1) is 1:1, and the other steps and parameters are the same as those in Example 1.
[0095] Results: Copolymer yield: >99%, hydrogenation yield: 85%, hydrogenation degree: >99%, hydride number average molecular weight (M n ):4.70×10 5 g / mol, molecular weight distribution (PDI): 2.8, and glass transition temperature is -56.8° C. The mechanical properties of the hydrogenated product are shown in Table 10.
[0096] Table 10 Mechanical properties of hydrogenated products
[0097] Hardness / Shore A Tensile strength / MPa Elongation at break / % 300% modulus / MPa Tear strength N / mm 67 16.59 276.74 14.62 37.12
[0098] Example 10: This example differs from Example 1 in that the solvent in step (2) is replaced with n-hexane, and the other steps and parameters are the same as those in Example 1.
[0099] Results: Copolymer yield: >99%, hydrogenation yield: 84%, hydrogenation degree: >99%, hydride number average molecular weight (M n ):4.80×10 5 g / mol, molecular weight distribution (PDI): 2.5, and glass transition temperature is -47.5° C. The mechanical properties of the hydrogenated product are shown in Table 11.
[0100] Table 11 Mechanical properties of hydrogenated products
[0101] Hardness / Shore A Tensile strength / MPa Elongation at break / % 300% modulus / MPa Tear strength N / mm 63 14.95 299.32 13.54 35.82
[0102] Comparative Example 1: This embodiment differs from Example 1 in that the hydrogenation temperature in step (2) is increased to 150° C. and the reactor pressure is increased to 100 mbar. Other steps and parameters are the same as those in Example 1.
[0103] Results: Copolymer yield: >99%, hydrogenation yield: 63%, hydrogenation degree >85%, hydride number average molecular weight (M n ):1.2×10 5 g / mol, molecular weight distribution (PDI): 3.6, and glass transition temperature is -45.6°C. The product after hydrogenation is in powder form and the mechanical properties cannot be tested.
[0104] The above merely describes preferred specific embodiments of the present application, which are based on different implementations of the overall concept of the present application, and the protection scope of the present application is not limited thereto. Any changes or replacements that are easily conceived by those skilled in the art within the technical scope disclosed by the present application shall be covered by the protection scope of the present application. Therefore, the protection scope of the present application should be subject to the protection scope of the claims.
Claims
1. A high performance hydrogenated butadiene-isoprene elastomer characterized in that, The elastomer has a number average molecular weight of 10,000-700,000 g / mol, a molecular weight distribution of 1.0-5.0, a hydrogenation degree of >90%, and a glass transition temperature range of -80 to -20℃.
2. The elastomer of claim 1, wherein, The elastomer has a number average molecular weight of 10,000-500,000 g / mol, a molecular weight distribution of 2.1-2.8, a hydrogenation degree of >92%, and a glass transition temperature range of -70 to -25℃.
3. The elastomer of claim 1, wherein, The elastomer has a mechanical property of Shore A hardness >40, a tensile strength >10 MPa, an elongation at break >270%, a 300% modulus >10 MPa, and a tear strength >20 N / mm.
4. The elastomer of claim 3, wherein, The elastomer has a mechanical property of Shore A hardness >46, a tensile strength >13 MPa, an elongation at break >280%, a 300% modulus >12 MPa, and a tear strength >23 N / mm.
5. Process for the preparation of an elastomer according to any one of claims 1 to 4, characterized in that, The method comprises the following steps: The butadiene-isoprene copolymer is dissolved in a solvent to form a mother liquor, which is then added to a high-temperature reaction kettle under an argon atmosphere, followed by the addition of Wilkinson catalyst and triphenylphosphine. After replacing the gas in the kettle with hydrogen, the hydrogenation reaction is carried out at a rotation speed of 100-1000 rpm, a pressure of 10-90 mbar, and a temperature of 60-150℃ for 1-24 h. After the reaction is completed, the precipitate is cooled, precipitated, and vacuum-dried at room temperature to obtain the elastomer.
6. The method of claim 5, wherein, The block ratio of isoprene to butadiene in the butadiene-isoprene copolymer is (1-9):
1.
7. The method of claim 5, wherein, The concentration of the butadiene-isoprene copolymer in the mother liquor is 1-3 wt%.
8. The method of claim 7, wherein, The concentration of the butadiene-isoprene copolymer in the mother liquor is 2 wt%.
9. The method of claim 5, wherein, The method for preparing the butadiene-isoprene copolymer comprises the following steps: Under anhydrous and anaerobic conditions, an iron catalyst, a cocatalyst, an olefin monomer, and an anhydrous solvent are added to a reactor, and the polymerization reaction is stirred at 0-100℃ for 10-120 min. After the reaction is completed, a quenching agent and an anti-aging agent are added, and the product is washed and vacuum-dried to constant weight to obtain the copolymer.
10. The method of claim 9, wherein, The iron catalyst is any one of the following structural formulas:
11. The method of claim 9, wherein, The molar ratio of the olefin monomer to the iron element in the iron catalyst is (10-20000):
1.
12. The method of claim 11, wherein, The molar ratio of the olefin monomer to the iron element in the iron catalyst is (260-6600):1, the polymerization reaction temperature is 30℃, and the reaction time is 30 min.
13. The method of claim 5, wherein, The Wilkinson catalyst is chloro rhodium triphenylphosphine, the molar ratio of chloro rhodium triphenylphosphine to triphenylphosphine is 1:(1-20), and the solvent is one or more of toluene, xylene, n-hexane, and cyclohexane.
14. The method of claim 13, wherein, The molar ratio of chloro rhodium triphenylphosphine to triphenylphosphine is 1:9, the hydrogenation reaction temperature is 100-120℃, the pressure is 60-80 mbar, the rotation speed is 660 rpm, and the reaction time is 16 h.
15. The elastomer of any one of claims 1-4 for use in the field of viscosity index improvers, automobile parts, and insulating materials.
